2019
DOI: 10.3390/polym11061034
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural Modification of PEDOT:PSS for High Charge Carrier Collection in Hybrid Frontal Interface of Solar Cells

Abstract: In this work, we propose poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) material to form a hybrid heterojunction with amorphous silicon-based materials for high charge carrier collection at the frontal interface of solar cells. The nanostructural characteristics of PEDOT:PSS layers were modified using post-treatment techniques via isopropyl alcohol (IPA). Atomic force microscopy (AFM), Fourier-transform infrared (FTIR), and Raman spectroscopy demonstrated conformational changes and nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 44 publications
1
29
0
3
Order By: Relevance
“…The PSS on the PEDOT:PSS allows it to be dispersed in solvents, but its conductivity is much lower than that of ITO by about three orders of magnitude, which makes it less appropriate for optoelectronic applications [2,6,17]. Therefore, the characteristics of PEDOT:PSS should be modified, by applying physical or chemical post-deposition treatments, to increase its conductivity [2,[20][21][22]. Some ways in which these properties can be increased include solvent treatment [20,[23][24][25], doping with additional organic compounds, with boiling points higher than that of the water, into the aqueous solution [2], and adding ionic surfactants into the aqueous solution [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSS on the PEDOT:PSS allows it to be dispersed in solvents, but its conductivity is much lower than that of ITO by about three orders of magnitude, which makes it less appropriate for optoelectronic applications [2,6,17]. Therefore, the characteristics of PEDOT:PSS should be modified, by applying physical or chemical post-deposition treatments, to increase its conductivity [2,[20][21][22]. Some ways in which these properties can be increased include solvent treatment [20,[23][24][25], doping with additional organic compounds, with boiling points higher than that of the water, into the aqueous solution [2], and adding ionic surfactants into the aqueous solution [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the characteristics of PEDOT:PSS should be modified, by applying physical or chemical post-deposition treatments, to increase its conductivity [2,[20][21][22]. Some ways in which these properties can be increased include solvent treatment [20,[23][24][25], doping with additional organic compounds, with boiling points higher than that of the water, into the aqueous solution [2], and adding ionic surfactants into the aqueous solution [26].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that the varied properties of AN10, AN11, and AN13 induce the different degree of polymerization which affects the carrier mobility of PEDOT:PSS [54,58,59]. Based on the above result, by mixing an optimized amount of neutral and acidic PEDOT:PSS, the AN11 PEDOT:PSS is expected to exhibit enhanced charge carrier mobility because of improved conjugation and polymerization with π-π stacking structure which improves the electrical properties of PSCs.…”
Section: Degree Of Polymerization 2mentioning
confidence: 57%
“…In addition, AFM topography images were obtained for different PEDOT:PSS spin-coated films (AN10, AN11, and AN13) to allow studying the possible changes in morphology at the nanometer scale ( Figure 4). The root-mean-square (RMS) roughness values of AN10, AN11, and AN13 were To compare the degree of electrochemical polymerization occurs at the α,α'-positions in polythiophene [53], the polymerization degree of PEDOT was evaluated from the ratio of integration of the infrared bands [54]. The average degree of polymerization of PEDOT can be evaluated using the equation as follows [55][56][57],…”
Section: Degree Of Polymerization 2mentioning
confidence: 99%
“…This demonstrated that the polymer in PEDOT:PSS was appropriately processed without decomposition. The degree of polymerisation (which occurs at the α and α′ positions of polythiophene) was determined 95 by evaluating the degree of polymerisation (PEDOT) by comparing the integration ratio of certain infrared bands according to the following equation: 93 []Degree of polymerization=20.25em[]0.25em()R0R+20.25em where the degree of polymerisation is determined by the following parameters: (a) R means the integrated intensity ratio within a specific band (685 and 823 cm −1 ). This corresponds to C‐S‐C coupling (stretch vibration).…”
Section: Resultsmentioning
confidence: 99%